Dynamics of adsorptive systems for heat transformation : optimization of adsorber, adsorbent and cycle /: optimization of adsorber, adsorbent and cycle. (2018) - Sapienza, Alessio; Frazzica, Andrea; Freni, Angelo; Aristov, Yuri
No abstract available